Development of practice principles for the management of ongoing suicidal ideation in young people diagnosed with major depressive disorder - Rice, Simon M (SAGE Open Med, 2014)
OBJECTIVES: There is a lack of clear guidance regarding the management of ongoing suicidality in young people experiencing major depressive disorder. This study utilised an expert consensus approach in identifying practice principles to complement relevant clinical guidelines for the treatment of major depressive disorder in young people. The study also sought to outline a broad treatment framework for clinical intervention with young people experiencing ongoing suicidal ideation. METHODS: In-depth focus groups were undertaken with a specialist multidisciplinary clinical team (the Youth Mood Clinic at Orygen Youth Health Clinical Program, Melbourne) working with young people aged 15–25 years experiencing ongoing suicidal ideation. Each focus group was audio recorded and transcribed verbatim using orthographic conventions. Principles of grounded theory and thematic analysis were used to analyse and code the resultant data. RESULTS: The identified codes were subsequently synthesised into eight practice principles reflecting engagement and consistency of care, ongoing risk assessment and documentation, individualised crisis planning, engaging systems of support, engendering hopefulness, development of adaptive coping, management of acute risk, and consultation and supervision. CONCLUSIONS: The identified practice principles provide a broad management framework, and may assist to improve treatment consistency and clinical management of young people experiencing ongoing suicidal ideation. The practice principles may be of use to health professionals working within a team-based setting involved in the provision of care, even if peripherally, to young people with ongoing suicidal ideation. Findings address the lack of treatment consistency and shared terminology and may provide containment and guidance to multidisciplinary clinicians working with this at-risk group.